Propagation and Purification of High-Titer Human Cytomegalovirus - Chambers, R. W. (1971)
High-titered yields of human cytomegalovirus (CMV), strain AD 169, were produced in WI-38 cells in large roller bottles. Maximum plaque titers were observed by the 4th day after infection at which time infectivity in the medium was 200 times greater than that associated with the cells. Virus released into the medium was recovered by sedimentation in a sucrose gradient in a continuous-flow centrifuge rotor. Maximal viral infectivity was found at a sucrose concentration of 42%, equivalent to a density of 1.18 g/cm(3). Deoxyribonucleic acid extracted from these preparations was about 80% viral and 20% cellular as judged by equilibrium centrifugation in cesium chloride density gradients.